2014
DOI: 10.4269/ajtmh.13-0603
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of a TaqMan-Based Real-Time PCR for the Detection of Mycobacterium tuberculosis-Complex in Human Sputum

Abstract: Abstract. Real-time polymerase chain reaction (qPCR) was optimized for detecting Mycobacterium tuberculosis in sputum. Sputum was collected from patients (N = 112) with suspected pulmonary tuberculosis, tested by smear microscopy, decontaminated, and split into equal aliquots that were cultured in Lö wenstein-Jensen medium and tested by qPCR for the small mobile genetic element IS6110. The human ERV3 sequence was used as an internal control. 3 of 112 (3%) qPCR failed. For the remaining 109 samples, qPCR diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
(24 reference statements)
2
24
0
Order By: Relevance
“…Second, these assays also gave qPCR products for some of the NTM reference strains; therefore, they could only be applied after M. tuberculosis presence confirmation, for instance with our previous qPCR protocol for TB detection. 25 In summary, the qPCR methods proposed in this study showed high specificity and sensitivity for the targeted mutations, short turn-around time, and relatively low cost that shows its potential for improving TB diagnosis and treatment. Therefore, further evaluation is needed to determine its diagnostic reliability in specimens in operational settings, and potential usefulness for routine clinical practice in settings with qPCR facilities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, these assays also gave qPCR products for some of the NTM reference strains; therefore, they could only be applied after M. tuberculosis presence confirmation, for instance with our previous qPCR protocol for TB detection. 25 In summary, the qPCR methods proposed in this study showed high specificity and sensitivity for the targeted mutations, short turn-around time, and relatively low cost that shows its potential for improving TB diagnosis and treatment. Therefore, further evaluation is needed to determine its diagnostic reliability in specimens in operational settings, and potential usefulness for routine clinical practice in settings with qPCR facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both multiplex assays must be run after TB confirmation, for example, by the PCR previously standardized by our laboratory. 25 Abnormal or double melting peaks should alert for a possibly unnoticed presence of heteroresistance or mixture with NTM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations